Double-diffusive natural convection in a triangular solar collector - Rahman, M. M.; Öztop, Hakan Fehmi; Ahsan, A.; Kalam, M. A.; Varol, Y. (Pergamon-Elsevier Science Ltd, 2012)
The current study deals with mathematical study for natural convection flow resulting from the combined buoyancy effects of thermal and mass diffusion inside a triangular shaped solar collector. The solution is performed assuming the isothermal and isoconcentration boundary conditions of absorbers and covers of collector. The two-dimensional governing equations for the physical phenomenon are expressed in a velocity-pressure formulation, along with the energy and concentration balance equations. A finite element method is used to solve these equations. Effects of the thermal Rayleigh number and buoyancy ratio are presented by streamlines, isotherms, isoconcentration as well as local and mean heat and mass transfer rates for the aforesaid parameters. Comparison with the previously published work is made and found to be an excellent agreement. Particularly, the design for enhancing the performance of the collector is determined by examining the abovementioned results. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Solar collector; Finite element method; Absorbers and covers diffusion